Formação em psicopedagogia e docência na educação infantil contribuições, contradições e reflexões - Matos, Edneia Felix de (Editora Oficina Universitária, 2022)
It is with immense satisfaction that I received the invitation to write the back cover of such an important work that discusses the contribution of Psychopedagogy in Early Childhood Education. The book entitled "Training in psychopedagogy and teaching in early childhood education: contributions, contradictions and reflections" brings an important reflection on Psychopedagogy, a specialty that transits between the areas of health and education, and that is present for the understanding of the teaching-learning process in its subtleties, peculiarities, singularities, specificities and complexities as the author herself highlights in her text. The author brilliantly discusses the need for Psychopedagogy to be present in the didactics of Early Childhood Education teachers, since it can contribute to the understanding of learning deviations that can be detected early in preschoolers. Early Childhood Education teachers must be vigilant in the process of acquisition and development of language and learning, planning and developing specific actions to promote normal development and the detection of deviant learning processes and, in this sense, Psychopedagogy can help these teachers. In this way, I hope that a large number of educators will have access to this work, as it is essential and mandatory for all teachers interested in improving their educational practice. SIMONE APARECIDA CAPELLINI | UNESP Marília